Murder of a recluse - Dams, Jeanne M. (Dams, Jeanne M. Oak Park Village mystery, 2025)
July, 1926. Now happily married to lawyer Fred, Elizabeth Wilkins is ready for whatever married life throws at her. So when Fred comes home anxious about his new client, Caroline Dobbs, who's suspected of murdering her elderly Aunt Agatha, Elizabeth can't help getting involved. Caroline was seen arguing with her aunt at Agatha's farm on the outskirts of town the day she died by neighbour and local gossip-monger, Miss Edwards, but Fred is convinced of Caroline's innocence. Elizabeth joins the influential local Nineteenth-Century Women's club as she attempts to find out more about the Dobbs family, uncovering dark secrets and a potential link to her new 'contact', notorious mobster, Al Capone. Can she unravel the mystery in time to save Caroline from an unjust death sentence?